Estimating the Efficacy of a Commercial Phase I Inactivated Vaccine in Decreasing the Prevalence of Coxiella burnetii Infection and Shedding in Red Deer (Cervus elaphus) - González-Barrio, David; Ortiz, José Antonio; Ruiz-Fons, Francisco (Frontiers in Veterinary Science, 2017)
The red deer (Cervus elaphus) is a relevant reservoir for Coxiella burnetii in Iberia. C. burnetii genotypes that infect red deer also infect humans and domestic animals. Integrated control approaches that target both domestic and wild ruminants are, therefore, required in order to reduce C. burnetii infection risks in Iberia, especially in wildlife-livestock-human interaction scenarios. The aim of this field experiment was to test the efficacy of an inactivated phase I vaccine (IPIV; Coxevac®) when used to control C. burnetii shedding prevalence and burden in red deer as a tool to prevent transmission to livestock and humans. A semi-extensively bred red deer population in which C. burnetii is endemic was used as model of the Iberian context. Around 75% of the reproductive hinds (>1 year old; N=441) in the population were first vaccinated early in 2012, and were then revaccinated 3 weeks later; they were subsequently revaccinated biannually until January 2014. 75% of the yearling females left as replacement in 2012 and 2013 were vaccinated in June and revaccinated thereafter following the same protocol. 25% of the population, including the replacement females, was kept as a control group throughout the study. Changes in the humoral immune response after vaccination were estimated by analyzing sera collected at 10 different times between January 2011 and January 2015. The vaccinated and control hinds were surveyed at 2.5, 3.5 and 4.5 months after calving in 2012, 2013 and 2014 in order to collect vaginal swabs, milk and feces. The presence and burden of C. burnetii DNA in swabs, milk and feces was evaluated by means of real time PCR. Vaccination induced high antibody prevalence and levels. The proportion of animals shedding C. burnetii in vaginal secretions and milk did not change over time in the vaccination group with respect to the control group. In contrast, there was a significant reduction in the proportion of deer shedding C. burnetii in feces in both the vaccinated and control groups. The decrease in the proportion of fecal shedders coincided with a significant reduction in the incidence of infection of non-vaccinated yearling females in the population. This finding...